STEROIDAL SAPOGENINS - WITTBECKERE, L; WAGNER, RB; ULSHAFER, PR; RUOF, C H; MARKER, RE; GOLDSMITHD, PJ (PENNSYLVANIA STATE COLLEGE, SCHOOL OF CHEMISTRY AND PHYSICS, PENNSYLVANIA, PA, EUA, 1947)
1. Twelve new sapogenins and two new prosapogenins have been isolated. The original isolation procedure for each is described. Additional sources for these have been reported previously.3 2. Chemical interrelationships between these and the previously cha
J OPT SOC AM
Keywords: STEROIDAL SAPOGENINS; QUIMICA; BIOQUIMICA; BIOQUIMICA FISICA